STUDI KASUS PATOLOGI GIGI: KARIES PADA RANGKA MANUSIA ST1, SONG TERUS, PACITAN, JAWA TIMUR ( Dental Pathology Case Study: Caries On ST1 Human Remains, Song Terus, Pacitan, East Java) - Anita Tamu Ina; Dyah Prastiningtyas; Harry Widianto; Florent Détroit; Ferry Fredy Karwur; Andri Purnomo; Anne-Marie Sémah; François Sémah (BALAI ARKEOLOGI PAPUA, 2018)
Human remains found in Song Terus (Pacitan, East Java), known as ST1, presented an opportunity of in-depth study in reconstructing how human lived during Early Holocene period in the area. This article focuses on palaeopathological aspects by examining lesions of disease observable in bones and dentition of human remains found in archaeological context. The research done for this article focuses more on dental remains, as teeth are known to have durability and longevity as archaeological finds, and could also provide information on age-at-death, types of diet, and oral diseases which may occurred during a person’s life. Dental caries is one of the most common type of oral disease found in archaeological context. Research methods used are macroscopic observation and literature reference comparison.. Results showed there were nine dentition on this individual (from a total of 27 identified dentition) suffered from caries with various degree of severity. Other types of oral disease noted during observation and analysis were periodontal disease. ST1 might have been suffering from severe caries due to lack of oral hygiene, as well as minimum dental treatment towards emerging oral disease. Nevertheless, these diseases did not seem to be directly caused by ST1’s dietary habit during lifetime. ABSTRAK Temuan rangka manusia ST1 di Song Terus (Pacitan, Jawa Timur) memberikan peluang untuk menelusuri lebih jauh pola kehidupan manusia pada periode Holosen Awal di wilayah ini. Artikel ini berfokus pada aspek paleopatologi yang merupakan salah satu kajian ilmu dalam menelusuri jejak kehidupan manusia di masa lalu melalui penyakit pada tulang dan gigi manusia yang ditemukan dalam konteks arkeologi. Materi penelitian dalam artikel ini menitikberatkan pada gigi manusia yang merekam informasi mengenai masa hidup seseorang, termasuk aspek-aspek perkiraan usia saat mati, jenis makanan yang pernah dikonsumsi, dan penyakit yang pernah diderita. Kasus patologi berupa karies menarik untuk diteliti sebab penyakit ini merupakan salah satu kasus yang umum ditemukan pada sisa rangka manusia. Metode penelitian yang digunakan adalah observasi makroskopis dan metode pustaka. Hasil analisis menunjukkan bahwa dari 27 gigi tersisa pada individu ST1, terdapat sembilan gigi yang terdeteksi mengalami karies dan beberapa gigi lain yang menderita penyakit periodontal. Karies pada individu ini tampak disebabkan oleh mikro-organisme yang berkembang di dalam mulut akibat minimalnya perawatan kesehatan gigi dan mulut, serta tidak berhubungan langsung dengan asupan nutrisi yang dikonsumsi oleh individu ini pada masa hidupnya.